Sorption characteristics of banana slices (Musa paradisiaca L.) var. Raja Nangka by gravity method - La Choviya Hawa; Anang Lastrianto; Tanti Nirwana Tambunan (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2018)
Banana Raja Nangka (Musa paradisiaca L.) is a type of banana having a low economic value compared to other bananas due to its slight sour taste. Alternative valorisation of the banana is to make is into banana flour. Drying of banana slices var. Raja Nangka is an important factor to produce good quality of banana flour product. Drying is influenced by water content, water activity (aw), relative humidity (RH), moisture content balance, temperature, type of drying, drying rate, etc. The thermodynamic relationship between aw and moisture content balance of food products at constant temperature and pressure can be described by the behavior of moisture sorption isotherm.This research used a static gravimetric method composed of two treatment include desorption and adsorption samples at five levels of aw conditioned by using 5 g saturated salts: KOH (0.0738), MgCl2 (0.3244), CaCl2 (0.6183), NaCl (0.7509), KCl (0.8362) and three levels of temperature (i.e. 30, 40, and 50°C) in triplicate. Analysis of moisture sorption isotherm was carried out by weighing the samples on a daily basis until moisture content balance is reached. Moisture content balance is then fitted by using Wgnuplot software and the curve display is plotted by SM4WIN software.The results of moisture sorption isotherm indicated that moisture content balance can be obtained within 10 days. The curve of water desorption and adsorption and the curve of hysteresis were well fitted in type II, known as sigmoid type. In the desorption sample, Xm was obtained at 30, 40 and 50°C with the values of 0.148, 0.096, 0.055 (kg water/kg solid) and the adsorption samples were 0.12, 0.059, 0.54 (kg water/kg solid), respectively. The C value of C in desorption sample was 66.18, 34.15, 23.70, while in adsorption samples were 67.88, 21.87, 75.53. The K values in desorption samples were 0.81, 0.86, 0.90 and in adsorption samples were 0.72, 0.89, 0.87.